Determination of the radical-scavenging activities and identification of anthocyanins from Hexalobus monopetalus ripe fruits - Arrounan Noba; Adama Hema; Elie Kabré; Bazoin Sylvain Raoul Bazié; Paulin Ouôba; Eloi Palé; Mouhoussine Nacro; Constantin M. Dabiré; Remy K. Bationo; Moumouni Koala (Chemistry Department, The University of Brawijaya, 2022)
A wild fruit from classified forest of Dindéresso was analyzed for total phenolics, flavonoids, anthocyanins compounds using the Folin-Ciocalteu reagent, spectrophotometric method of Zhishen and colleagues and by the differential pH method respectively. Free radical-scavenging activities of studied fruits extracts were estimated using diammonium 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonate) salt method. Three major anthocyanins were identified using high performance liquid chromatography coupled with spray ionization interface mass spectrometry. Three identified anthocyanins in fruit were reported to be cyanidin 3-O-(p-coumaroyl) glucoside, pelargonidin 3-O-glucoside and pelargonidin 3-O-rutinoside. In addition, H. monopetalus fruit contained of about 1165±3.1 mg of GAE per 100 g of fresh fruit, 4490±20.2 mg of QE per 100 g of fresh fruit, and 36±0.17 mg of cyanidin 3-O-glucoside equivalents per 100 g of fresh fruit. Total anthocyanin extract had an EC50 = 4.24 mg per mL and a TEC50 time of 21 minutes (intermediate reaction). This free radical-scavenging activity was very low compared to those of the references used (0.024 and 0.034 mg/mL respectively for ascorbic acid and Trolox). The low antiradical activity and reactivity of the H. mucronata extract could be explained by several factors. In any case, fruits of this species were potential sources of natural bioactive substances having beneficial effects on the health of consumers.